ShopeePay Later Restrictions in Aceh: A Study of Qanun No. 11 of 2018 and Consumer Protection - Syahrizal, Teuku Muhammad; Najla, Najla; Rusdi, Rusdi (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
The development of fintech and e-commerce in Indonesia has triggered a transformation in consumer behavior, one of which is through Paylater services that provide instant access to financing. However, in Aceh, these services are inaccessible due to the implementation of Aceh Qanun No. 11 of 2018 on Sharia Financial Institutions, which requires all financial activities to be based on sharia principles and prohibits the practices of usury, gharar, and maisir. This study aims to analyze the relationship between the Qanun on Sharia Financial Institution and the protection of Muslim consumers in the context of fintech and e-commerce development, with a focus on the case of ShopeePay Later restrictions. The research method employed is a descriptive qualitative approach, utilizing a literature study and regulatory analysis. The findings indicate that the restrictions on ShopeePay Later in Aceh represent not only the enforcement of local law but also a strategy to safeguard Muslim consumers from non-Sharia financial practices. These results confirm that the Qanun on Sharia Financial Institution functions as both a legal instrument and a mechanism for securing Islamic values in digital transactions. Furthermore, this regulation encourages fintech and e-commerce innovation to deliver Sharia-based products, so that consumer protection does not become an obstacle but rather an opportunity.